A Clinical Study of Ninjin'yoeito With Regard to Frailty - Sakisaka, Naoya; Mitani, Kazuo; Sempuku, Sadahiro; Imai, Tamaki; Takemoto, Yoshinori; Shimomura, Hiroaki; Ushiroyama, Takahisa (Frontiers in Nutrition, 2018)
Frailty in older people is strongly associated with poor nutrition, which is particularly important in the present-day superaging society. This study initially investigated a number of cases of frailty where there was a speedy recovery after administration of a dual deficiency of qi and blood preparation, ninjin'yoeito (NYT), formulated for frail patients who suffer from kiketuryokyo status. Based on these observations, a more extensive investigation involving a greater number of cases was completed. The findings of the effects of NYT on frailty are reported here.